Azobenzene dye-coupled quadruply hydrogen-bonding modules as colorimetric indicators for supramolecular interactions - Zhang, Yagang; Zimmerman, Steven C. (Beilstein Journal of Organic Chemistry, 2012)
The facile coupling of azobenzene dyes to the quadruply hydrogen-bonding modules 2,7-diamido-1,8-naphthyridine (DAN) and 7-deazaguanine urea (DeUG) is described. The coupling of azobenzene dye 2 to mono-amido DAN units 4, 7, and 9 was effected by classic 4-(dimethylamino)pyridine (DMAP)-catalyzed peptide synthesis with N-(3-dimethylaminopropyl)-N’-ethyl carbodiimide hydrochloride (EDC) as activating agent, affording the respective amide products 5, 8, and 10 in 60–71% yield. The amide linkage was formed through either the aliphatic or aromatic ester group of 2, allowing both the flexibility and absorption maximum to be tuned. Azobenzene dye 1 was coupled to the DeUG unit 11 by Steglich esterification to afford the product amide 12 in 35% yield. Alternatively, azobenzene dye 16 underwent a room-temperature copper-catalyzed azide–alkyne Huisgen cycloaddition with DeUG alkyne 17 to give triazole 18 in 71% yield. Azobenzene coupled DAN modules 5, 8, and 10 are bright orange–red in color, and azobenzene coupled DeUG modules 12 and 18 are orange–yellow in color. Azobenzene coupled DAN and DeUG modules were successfully used as colorimetric indicators for specific DAN–DeUG and DAN–UPy (2-ureido-4(1H)-pyrimidone) quadruply hydrogen-bonding interactions.
Keywords: azobenzene dye; colorimetric indicators; 7-deazaguanine urea (DeUG); 2,7-diamido-1,8-naphthyridine (DAN); polymer; quadruply hydrogen bonding; supramolecular